Muhasabah sebagai Pengembangan Psikologi Islam - musfichin, musfichin (Faculty of Ushuluddin and Humanities, 2023)
Muhasabah as a medium of self-improvement in all activities for future life. This research uses the Research and Development (R&D) Method starting with research and continuing with development. The first study aims to discover the concept of muhasabah by using a literature study that discusses Muhasabah and interviews with several figures who have mastered the field of religion. The second presents the dimensions of muhasabah. The results of the first study obtained an understanding that muhasabah is an individual's awareness to calculate and correct self-activities that have been and will be undertaken for better purposes. While the results of the second study indicate that muhasabah has three dimensions including: self-awareness, self-counting, and self-correction. The implications of this research are discussed in the context of the development of Islamic psychology. Keywords: Self Awareness, Self Counting, and Self Correcting